OPTIMASI PRODUKSI INDUSTRI TEKSTIL MELALUI PENERAPAN MODEL SIMPLEX PADA PROGRAM LINEAR - Muhamad Rizki Aditia; Qoidar Al Uzhma, Mario Bintang Saputra, Paduloh (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The textile industry in Indonesia plays a crucial role in the economy; however, operational challenges such as demand fluctuations and resource limitations often hinder production efficiency. This study aims to optimize the production of woven fabrics in a textile company using Linear Programming (LP) methods, specifically the Simplex model, to maximize profit and allocate resources optimally. The study focuses on production capacity allocation issues, such as limited spindle and loom hours. By applying LP, the research hopes to find an efficient solution in managing the production of two types of fabrics, namely T/C and 100% Cotton, while considering raw material limitations and available machine hours. The study uses data from PT. Argo Pantes in Tangerang, which produces woven fabrics with diflerent profit margins/ Unit. In the Simplex method, slack variables are added to convert inequalities into equations, enabling the search for optimal solutions iteratively. The expected result of this research is to determine the most profitable production quantity by maximizing the use of available production capacity. Overall, the application of this model is expected to improve production efficiency and company profits, as well as contribute to the development of optimization techniques in the manufacturing sector, particularly in textiles